OP0080 CXCL13 and CCL11 Serum Levels are Associated With Lymphoma Occurrence and Disease Activity in Primary Sjögren Syndrome: Data from the French Prospective Cohort Assessment. (9th June 2015) - Nocturne, G.; Seror, R.; Fogel, O.; Dieudé, P.; Dubost, J.J.; Fauchais, A.L.; Goëb, V.; Hachulla, E.; Larroche, C.; Le Guern, V.; Morel, J.; Perdriger, A.; et al.
Abstract : Background: Development of non-Hodgkin lymphoma (NHL) is one of the most severe complications associated with primary Sjogren's syndrome (pSS). Presence of ectopic germinal center (GC) in salivary glands biopsy is a predictor of NHL occurrence in pSS patients [1]. Objectives: Given the association between CCL11 and CXCL13 and ectopic GC, we decided to assess the link between these chemokines and B cell lymphoma in pSS patients. Methods: CCL11 and CXCL13 serum levels at inclusion were evaluated in 385 patients from the ASSESS cohort by multiplex assay. The association between serum chemokine levels, B cell biomarkers and subsets of patients was assessed using Spearman's test for continuous data and nonparametric Wilcoxon test for categorical data. Multivariate analyses were performed to identify parameters associated with lymphoma and disease activity. Results: 22 patients of the ASSESS cohort had a NHL (history of NHL [n=17] or future [n=5]). The median [IQR] serum levels of CCL11 and CXCL13 were 106.48 [69.33 - 149.85] pg/ml and 108.31 [58.88 – 200.13] pg/ml, respectively. Patients with lymphoma presented higher levels of CXCL13 compared to patients without lymphoma (p=0.006; trend for an association for CCL11 (p=0.056)). If we focus on the 5 patients who developed lymphoma subsequently after the dosage, serum CXCL13 levels was even higher: 584.76 [262.99 – 756.19] pg/ml and statistically different from patients without any lymphoma (108.31 [59.95 – 197.25], p=0.0014). Low C4 and BAFF levels were associated with NHL in the multivariate analysis (p=0.01 and p=0.0002 respectively). CCL11 and CXCL13 levels positively correlated with 3 B-cell biomarkers: rheumatoid factor, κ/λ free light chain ratio and β2-microglubulin. CXCL13 level was the only parameter associated with disease activity in the multivariate analysis. Conclusions: This study demonstrates a link between serum levels of CXCL13 and CCL11 and disease activity and lymphoma. This highlights the continuum between chronic B-cell activation, disease activity and lymphomagenesis in pSS patients. References: Theander et al, ARD, 2011 Disclosure of Interest: None declared